The Influence of Nutrition Education Through Tiktok on the Knowledge and Attitudes of Young Women in Efforts to Prevent Anemia in Medan City - Riski Sri Purwanti Pasaribu; Zulhaida Lubis; R. Kintoko Rochadi (Journal of Social Research, 2023)
The prevalence of anemia in Indonesia in adolescent groups since 2007 has continued to increase until in 2018 it showed a percentage of 32 percent. This shows that efforts to prevent anemia are still not carried out properly. The purpose of this study was to analyze the influence of nutrition education through Tiktok on the knowledge and attitudes of adolescent girls in efforts to prevent anemia in Medan City. The type of research used is a pseudo-experiment with a pretest-posttest control group design. The number of samples of this study was 39 people in each group so the number of respondents was 78 people. Before conducting data analysis, the Kolmogrov-Smirnov test was carried out and it was known that the data was not normally distributed, so the data analysis continued with the Wilcoxon test and Mann-Whitney test. The results of the study in the experimental group showed the average value of knowledge from 9.92 to 15.03 with a p-value = 0.001 (<0.005) and an average attitude value from 7.69 to 12.59 with a p-value = 0.001 (<0.005) which means that there is an influence of nutrition education through TikTok on the knowledge and attitudes of young women. The results of the study in the control group obtained the average value of knowledge from 9.95 to 13.46 with a value of p = 0.001 (<0.005) and an average value of attitude from 7.90 to 12.05 with a value of p = 0.001 (<0.005) which means that there is an influence of nutrition education through leaflets on the knowledge and attitudes of young women. Respondents' knowledge (mean rank = 47.49) and respondents' attitudes (mean rank = 44.97) in the experimental group had a higher value increase than the control group so it can be concluded that nutrition education through TikTok is more effective in increasing the knowledge and attitudes of adolescent girls in efforts to prevent anemia than through leaflets. Therefore, TikTok is expected to be used as a health promotion medium.